Analisis Konsep Kehendak Bebas dalam Pemikiran Santo Agustinus dan Implikasinya terhadap Tindakan Dosa Manusia (Jurnal Riset Rumpun Agama dan Filsafat, 2026)
This article examines the moral philosophy of Saint Augustine, focusing on the concept of free will and its implications for human sinful actions. The study aims to provide a philosophical and theological understanding of Augustine’s concept of free will and to analyze its correlation with human acts of sin. Augustine conceives of free will as a rational capacity inherent in human beings, enabling them to make conscious choices. In its essence, this freedom is oriented toward the good. However, due to the fallen condition of humanity, the will becomes disordered and is directed toward things that are lower than the highest good. Therefore, there exists an inherent correlation between free will and sinful action, wherein sin is understood as the manifestation of a misused will. Accordingly, the thought of Saint Augustine of Hippo affirms that free will is an essential gift that enables human beings to make conscious choices, including the choice to commit sin. Free will does not stand apart from moral reality; rather, it serves as the foundation for explaining that sin occurs as a result of the deviation of the human will from the highest good, namely God. Thus, it can be asserted that there is a clear, close, and inseparable correlation between Augustine’s concept of free will and human sinful action.